Development banks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
There is a special kind of investment bank in many ACP countries known as a development bank. As the name indicates, these banks were established to handle international development funds and are designed to coordinate the investment of such capital...